2022
DOI: 10.1111/sms.14138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of daily 3‐s maximum voluntary isometric, concentric, or eccentric contraction on elbow flexor strength

Abstract: The present study compared a 3‐s isometric maximal voluntary contraction (MVC), concentric MVC and eccentric MVC of the elbow flexors performed daily for 5 days a week for 4 weeks for changes in muscle strength and thickness. Young sedentary individuals were assigned to one of three training groups (n = 13 per group) that performed either 3‐s isometric, concentric, or eccentric MVC once a day for 20 days, or to a control group (n = 10) that had measurements without training. The participants in the isometric g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 21 publications
3
27
3
Order By: Relevance
“…The sample size was estimated from our previous study 4 showing 12% increase in maximal voluntary eccentric contraction (MVC‐ECC) torque of the elbow flexors after performing a single three‐second maximal eccentric contraction a day for 5 days a week for 4 weeks. Since we had not known a possible difference between the groups, we used an effect size based on the above to estimate the number of samples for a group to be enough for detecting a possible increase in MVC‐ECC torque after training.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The sample size was estimated from our previous study 4 showing 12% increase in maximal voluntary eccentric contraction (MVC‐ECC) torque of the elbow flexors after performing a single three‐second maximal eccentric contraction a day for 5 days a week for 4 weeks. Since we had not known a possible difference between the groups, we used an effect size based on the above to estimate the number of samples for a group to be enough for detecting a possible increase in MVC‐ECC torque after training.…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variables consisted of maximal voluntary isometric contraction (MVC‐ISO) torque at three different elbow joint angles (20°, 55°, 90°), concentric (MVC‐CON), and eccentric contraction (MVC‐ECC) torque at two angular velocities (30°/s, 180°/s), and biceps brachii and brachialis muscle thickness. Several MVC measurements were taken in accordance with our previous study 4 to examine whether any specifity of the training would be observed for other measurements than MVC‐ECC torque. These measurements were taken from the trained arm only, thus we did not investigate the cross‐education effect in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations